Traill 2018. A Trilingual !Xóõ Dictionary. !Xóõ – English – Setswana - Fehn, Anne-Maria (AAeO - Afrikanistik-Aegyptologie-Online, 2018)
Anthony Traill 2018. A Trilingual !Xóõ Dictionary. !Xóõ – English – Setswana,ed. by Andy Chebanne and Hirosi Nakagawa. Research in Khoisan Studies 37 Köln: Rüdiger Köppe